Molecular mechanisms involved in murine bone marrow erythropoietic response to acute anaemia by bleeding - Todaro, Juan Santiago (2013)
Fil: Todaro, Juan Santiago. Universidad Nacional del Nordeste. Facultad de Medicina; Argentina.